Desenvolvimento de compósitos de polímero ionomérico e metal baseados em poli(éter-éter-cetona) sulfonados - Blanco, Guilherme Eduardo de Oliveira (2023)
Ionic polymer-metal composites (IPMCs) are smart and bio-inspired materials that have a metal/polymer/metal sandwich structure. These are capable of deforming in response to electrical stimuli and vice versa, being promising in several applications, such as actuators, sensors, artificial muscles, and robotics. The ionomeric polymer most used for these purposes is Nafion®. However, this has a high cost, low water holding capacity, low performance at high temperatures, and is not environmentally friendly. Therefore, the development of alternative membranes is sought, among them, those based on sulfonated poly(ether-ether-ketone) (SPEEK). The insertion of sulfonic groups aims to add polar groups that make it hydrophilic and enable the ionic conduction required for these devices. Within this context, this work sought to analyze the viability of this polymer with different degrees of sulfonation (DS) and its use as IPMC. FTIR assays confirmed the successful insertion of sulfonic groups post-sulfonated, obtaining DS of 44, 72 and 91%. Electrochemical, electromechanical and water absorption kinetics tests were conducted. The main results indicate that the alternative IPMCs presented comparable performance and in some cases superior to Nafion®. It was observed that the increase in the degree of sulfonation was favorable to the electromechanical performance, with an increase in displacement values and displacement rate. The use of ionic liquid in conjunction with SPEEK was also analyzed, which presented favorable electromechanical sensing results, and these presented the ability to detect different trajectories and imposed speeds, reaching a sensing capacity of up to 1000 times greater than Nafion ®. Therefore, it was concluded that SPEEK-based IPMCs can potentially replace Nafion® and represent a lower-cost alternative.